Infantile epileptic spasms syndrome: an etiologic study of 361 patients with infantile epileptic spasms syndrome - Zhu, Linghui; Xia, Yuan; Ding, Hao; Zhang, Tong; Li, Jun; Li, Baomin (Frontiers in Pediatrics, 2025)
IntroductionInfantile Epileptic Spasms Syndrome (IESS) typically has a profound impact on the neurodevelopment of patients. The study on IESS indicates possible geographical variation in etiology and a lack of data from China. Our study intends to summarize the etiology of IESS and analyze its characteristics.MethodsA retrospective analysis was performed to gather clinical data from patients diagnosed with IESS at the Department of Neurology of Qilu Hospital of Shandong University and the Children's Hospital Affiliated to Shandong University between June 2017 to May 2024.ResultsA total of 361 patients with IESS were included, comprising 115 structural cases (31.9%), 37 genetic cases (10.2%), 32 genetic-structural cases (8.9%), 9 metabolic cases (2.5%), 3 infectious cases (0.8%), and 165 cases with unknown etiology (45.7%). No immunological cause was determined. The primary cause of the condition was linked to hypoxic-ischemic encephalopathy (HIE), with structural brain abnormalities following closely. The predominant pathogenic genes identified were TSC2, NF1, SCN8A, and KCNQ2. Male gender, preterm infants, low birth weight infants, and developmental regression in patients were associated with a higher likelihood of structural etiology. Patients exhibiting developmental regression before the commencement demonstrated inferior outcomes. Patients administered adrenocorticotropic hormone (ACTH) exhibited a higher likelihood of attaining seizure control, and those who responded favorably to the medication saw improved results.ConclusionThe predominant etiology of IESS is structural, succeeded by genetic factors, with significant pathogenic genes comprising TSC2, NF1, SCN8A, and KCNQ2. The genetic classifications exhibit geographic variability. Genetic and structural etiologies are frequently linked to an unfavorable prognosis. Genetic testing can help clarify the etiology of IESS when metabolic screening and brain MRI results are negative. The advancement of genetic testing is crucial for future targeted and individualized diagnosis and therapy.